Pengawasan Atas Penerimaan Pajak Hiburan dan Restoran: Studi Kasus di Dinas Pendapatan Daerah Kota Medan Tahun 2017-2021 - Alfarabi, Hazrya Rachma; Nasution², Yenni Samri Juliaty (Economic Reviews Journal, 2024)
Entertainment tax, restaurant tax is one of the taxes that has a very big role in increasing Medan City Regional Tax revenue. With the development of this increasingly modern era, from year to year there are more and more developments of entertainment venues and restaurants in the city of Medan. This study aims to analyze how the supervision of revenue from entertainment tax and restaurant tax is carried out by the Medan City Revenue Service. This research was conducted at the Medan City Revenue Service, which is located at Jalan Abdul Haris Nasution No. 32 Medan, Johore. The variables in this study are entertainment tax, restaurant tax and monitoring of tax revenue through the level of effectiveness of tax revenue. The results of the analysis show that entertainment tax supervision at the Medan City Revenue Service is still ineffective with effectiveness below 80%. Entertainment and restaurant tax revenue in Medan City has not reached the predetermined target due to the lack of awareness of taxpayers in paying their taxes and the lack of supervision of tax revenues by tax officials and related agencies. Keywords: Supervision, Entertainment and Restaurant Tax